The link between the adjusted misery index and crime in the Philippines - Sabino II, Robert Dennis E.; Mendoza, Adrian R. (Quezon City School of Economics, University of the Philippines Diliman, 2023)
This study analyzes the relationship between the adjusted misery index and crime rate in the Philippines from 1978 to 2008. The adjusted misery index is an extension of Okun’s [1970] original indicator, which combined inflation and unemployment rate to measure general economic well being. In this study, we add underemployment rate to the original misery index to more accurately capture the labor market conditions in the country. We adopt the Cantor-Land [1985] model to determine the relationship between the misery index and crime rate. According to the model, macroeconomic conditions affect crime via two contrasting effects: the motivational and opportunity effects. Worsening economic conditions may motivate more individuals to commit crime to maintain their standard of living. In contrast, the opportunity effect argues that unemployed individuals spend more time at home, which reduces their vulnerability to commit crime or be victims of crime. We use Johansen cointegration analysis and the vector error correction model (VECM) to identify the short-run and long-run dynamics between the adjusted misery index and crime rate in the Philippines. Our results suggest both short-run and long-run causal links from the adjusted misery index to crime. In particular, the adjusted misery index has a positive effect on crime rate in the Philippines, suggesting a stronger motivational than opportunity effect. The policy implication is non-trivial: if macroeconomic performance is a significant determinant of crime rates, then improving macroeconomic conditions may be used to reduce criminal activities in the country.
Thesis (BS Economics) - - University of the Philippines Diliman
Keywords: Unemployment and crime -- Philippines